Value of Knowledge Management and Communities of Practise in Mergers and Acquisitions: Identifying the determinants - Bains, Ravi (2010)
Whilst many mergers and acquisitions (M&As) are conducted in order to acquire another firm’s knowledge base, the speed of integration is crucial to the success of any M&A as this stage causes considerable disruption to the organisation which can lead to the failure of any merger or acquisition. Facilitating the free flow of knowledge across the organisational boundary between the acquired and acquiring firm can help integrate the two knowledge bases more effectively and lead to the creation of new knowledge. Effective Knowledge Management (KM) is crucial to this process and KM tools and techniques can have added benefit in the field of M&As. As the majority of organisational knowledge is tacit and cannot be articulated, effective processes need to be implemented to enable tacit knowledge transfer across the boundary between groups and individuals. Communities of Practise (CoPs) can provide the key here to unlocking the value of M&As which will lead to better integration of the two firms. As the informal structure of CoPs easily allows interaction and collaboration between the acquired and acquiring unit, such a tool can facilitate the free dissemination of knowledge across a newly merged organisation which can help integrate the workforce and amalgamate the two knowledge bases. The success of the adoption of KM principles, tools and techniques by newly merged organisations is dependent on the effective management of the human resources during this change period. Employee resistance needs to be minimised here by addressing barriers to integration and barriers to knowledge sharing. Only once these barriers have been addressed can efforts be directed towards creating enabling conditions that will maximise the success of a KM initiative in a newly merged organisation through the development of CoPs.